Tujuan Konstruksi Gender : Terkait Pembagian Peran dan Tanggung Jawab - Alfarel, Rizqi; Farah, Naila (Equalita: Jurnal Studi Gender dan Anak, 2024)
The understanding of gender in today's media is very diverse due to misconceptions and is even often considered to be liberal. In the context of gender, the idea of libertÃ© is understood as an unconditional freedom where individual freedom surpasses social rights and responsibilities. Thus, in this humorous era, we are allowed to identify ourselves as non-binary groups, such as transgender or homosexual individuals. Essentially, the purpose of gender construction is an effort to divide labor, which concerns the roles and responsibilities between men and women to work together in forming an ideal family unit. Instinctively, we are aware that there are general, widespread differences between men and women. Both are distinct entities or opposites, yet they create harmony. This is because the family is a moral institution, both in terms of instilling and developing moral values. The method used in this journal writing is a digital library study, where the process involves referencing articles and digital media content related to the discussed issue.